(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gay relation or Homosexuality is a romantic attraction, sexual attraction or sexual behaviour between members of the same sex or gender. It also denotes to a person’s sense of identity based on those attractions, related manners, behaviours and membership in a community of others who share those attractions. During the period of 1980s and afterwards most of the people accepted the extensive concept of homosexuality or gay relation. The theme of homosexuality was frequently merged into otherwise traditional speculative fiction stories works apparent that went beyond simple representation of homosexuality to systematic consideration of significant issues relevant to LGBT community. This development was helped by growing number of openly gay or lesbian authors. Specialist gay publishing presses and a number of awards recognizing LGBT achievements in the genre emerged, and by the twenty first century obvious homophobia was no longer considered acceptable by most readers of speculative fiction. At the same time, there was an increase in representation of homosexuality within non-literary forms of speculative fiction. From the twentieth century till now, Film makers, and writers continues several times in highlighting the LGBT themes. This effort helps them to gain media attention and controversy while the perceived lack of sufficient representation, along with unrealistic depictions, arouses criticism from LGBT sources.